EMPRUNTS LEXICAUX EN LOBIRI, LANGUE GUR DE CÔTE D’IVOIRE / LEXICAL BORROWINGS IN LOBIRI, A GUR LANGUAGE OF CÔTE D’IVOIRE / ÎMPRUMUTURI LEXICALE ÎN LOBIRI, LIMBA VOLTAICĂ DIN COSTA DE FILDEŞ - Sib Sié Justin (Studii si Cercetari Filologice: Seria Limbi Straine Aplicate, 2017)
Language Contacts cause them to maintain or evolve through analogy and borrowing. The Lobiri (gur language Ivory Coast) shares its linguistic environment with local Ivorian languages such as teen; Koulango, Dioula ...It is also in contact with Indo-European languages such as French and English. The need to name or to represent realities that do not appear in its language environment prompts speakers of Lobiri to incorporate words and phrases related to technological innovation, social development, language and trade. Thus, we see the rapid development of a linguistic phenomenon that contributes to the fertilization of the lexical stock of Lobiri. As such, occured phonological, morphological, semantic and syllabic particularities. The objective of the study is to describe the impact of loans on the Lobiri